I can’t feel your face: callous-unemotional traits, social anxiety, and approach-avoidance behaviour in conduct disorder - Laura M. Derks; Eni S. Becker; Mike Rinck; Martin Holtmann; Tanja Legenbauer; Wolf-Gero Lange (Child and Adolescent Psychiatry and Mental Health)
Abstract Background and objectives Conduct disorders are associated with deficits in interpersonal behaviour. Both, callous-unemotional traits and social anxiety are often elevated in patients with conduct disorder and are associated with aggressive approach or disproportional avoidance. Previous studies have focused mainly on questionnaire reports of interpersonal behaviour, whereas direct explicit and implicit interpersonal behaviour in social contexts has not been considered sufficiently. Therefore, explicit and implicit interpersonal behaviour were investigated in children and adolescents with conduct disorder in the current study. Methods Forty male adolescent inpatients with conduct disorder and 30 typically developing controls (M age = 12.5, SD = 1.39) took part in a virtual reality task in which they approached virtual agemates, displaying different facial expressions under the pretext of a cover story while interpersonal distance and walking speed were assessed (indirect condition). In addition, they were asked to move to a comfortable distance for conversation toward the agent (direct condition). Callous-unemotional traits and social anxiety were assessed via questionnaires. Results In the indirect condition, no differences between the groups emerged. In the direct condition, typically developing children adjusted their interpersonal distance to the respective expression that the virtual classmate displayed. They showed significantly greater interpersonal distances to angry classmates than to happy classmates. In contrast, conduct disorder patients’ interpersonal distance, did not differ between emotions. Interpersonal distance preferences were also associated with social anxiety and callous-unemotional traits. Conclusion The findings suggest that conduct disorder patients fail to adjust their interpersonal behaviour to the facial expression of social interaction partners and that this is associated with social anxiety and callous-unemotional traits. A lack of adjustment to social cues might contribute to and maintain problems with peers in individuals with conduct disorder.